The paradox of progress: structured football, self-efficacy, and the Dunning-Kruger effect – a randomized controlled trial - Aune, Tore; Knutsen, Jarl Magnus; Douglass, Bradley; Pedersen, Paul Harald; Lagestad, Pål (Frontiers in Psychology, 2025)
IntroductionStructured sports interventions are widely believed to enhance self-efficacy and emotion regulation in children. However, few randomized controlled trials (RCTs) have rigorously tested these assumptions, and even fewer have explored the psychological mechanisms underlying unexpected or paradoxical outcomes. This study investigated the effects of an 11-session football-based intervention on social self-efficacy, perceived competence, and emotion regulation strategies in children aged 9–12, with the potential influence of the Dunning-Kruger Effect.MethodsOne hundred and five children (68 in the intervention group, 37 in the control group) participated in a 4-month RCT. The intervention group received 11 structured football sessions (75 min each) incorporating cognitive-behavioral skills training. The outcomes related to social self-efficacy, perceived competence, cognitive reappraisal, and expressive suppression were measured at pre- and post-test using validated self-report scales. Mediation analysis examined whether cognitive reappraisal accounted for the intervention effects.ResultsContrary to the expectations, the control group reported significantly higher social self-efficacy and perceived competence at post-test than the intervention group. Furthermore, cognitive reappraisal did not mediate the relationship between group assignment and self-efficacy. No significant correlations were found between cognitive reappraisal and expressive suppression. We argue that these findings may reflect the Dunning-Kruger effect, whereby intervention participants, having gained new skills and self-awareness, became more critical and accurate in their self-assessments, resulting in lower self-reported efficacy and competence.DiscussionConsidering the results, we conclude that structured football interventions may inadvertently heighten children’s self-awareness of their limitations, leading to more modest self-evaluation of efficacy and competence. These findings underscore the importance of considering meta-cognitive shifts and the Dunning-Kruger effect when interpreting intervention outcomes, suggesting that self-report measures may not fully capture genuine skill gains in youth interventions.